Modelling and Simulation of Drag Forces of Non-spherical Particles Moving Towards a Surface in Polymer Melt Flows - Agaliotis, Eliana Mabel (2017)
This work deals with the drag forces acting on non-spherical particles translating normal to a surface in a polymer melt in which the particle–surface distance is small compared with particle dimension in the flow direction. Hence, drag forces will be modified as a function of distance. A finite element model was used in order to calculate the drag forces for the motion of particles. Several non-spherical particles geometries were simulated towards a plane surface wall. The fitting of the numerical results with empirical expressions presented two very well defined tendencies. Up to a given value of particle-wall distance the influence of the wall was strong, hence it was necessary to apply a correction to the analytical calculations. In addition, the relevance of the shape of the channel between the particle and the sink was demonstrated. The computational results provided a clear benefit to validate empirical approaches using analytical approximations.